Writing Anxiety For The Essay Writing Course At English Education Study Program Of UKI Toraja - Nehru Pasoloran Pongsapan (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2022)
The aims of the research were the researcher wanted to find out what are the factors affecting the Caused Writing Anxiety for the Essay Writing Course at English Education Study Program of UKI Toraja and what is the most factor Caused Writing Anxiety for the Essay Writing Course at English Education Study Program of UKI Toraja. In analyzing the data of this research, the researcher employed quantitative method. The subjects of this research were the fifth semester students at English Education Study Program of UKI Toraja. There were 120 the fifth semester students of English education study program of UKI Toraja academic year 2021/2022. There were twenty one students as the samples in this research chosen by using purposive sampling technique The data of those research was collected by doing interview supported by questionaire through google form. The obtained data were analyzed by likert scale. The finding obtained from the analyses of the related data show that the students faced three factors that caused writing anxiety (communication apprehension, test anxiety, and fear of negative evaluation), and the most factor was communication apprehension.